Korelacja dźwięczności/bezdźwięczności w systemie konsonantycznym ukraińskich gwar nadsańskich - Kołodyńska, Tatiana (Acta Polono-Ruthenica, 2012)
The article discusses issues concerning consonantism in the Ukrainian dialects over the territory of river San In Poland. Detailed analysys was put on the theme of correlation of conso- nant system in the end position of prefix, middle of the word, end of the word and the liaison position before voiced and voiceless consonants. Voiced and voiceless correlation occours in many south-western Ukrainian dialects and also in analyzed dialects over the territory of river San. The most characteristic feature of dialects over territory of river San is the less of consonant voicing which is supported by the influence of Polish language. Therefore, there are phonemes that have no counterparts correlation so they are not forming a binary pair.